Men With Late Effects of Polio Decline More Than Women in Lower Limb Muscle Strength: A 4‐Year Longitudinal Study. Issue 11 (12th May 2015) - Flansbjer, Ulla‐Britt; Brogårdh, Christina; Horstmann, Vibeke; Lexell, Jan
Abstract: Background: In persons with prior paralytic poliomyelitis, progressive muscle weakness can occur after a stable period of at least 15 years. Knowledge is limited about which factors influence changes in lower limb muscle strength in these persons. Objective: To assess changes in lower limb muscle strength annually over 4 years in persons with late effects of polio and to identify prognostic factors for changes in muscle strength. Design: A prospective, longitudinal study. Setting: University hospital outpatient program. Participants: Fifty‐two ambulant persons (mean age ± standard deviation: 64 ± 6 years) with verified late effects of polio. Methods: Mixed linear models were used to analyze changes in muscle strength and to identify determinants among the following covariates: gender, age, age at acute polio infection, time with late effects of polio, body mass index, and estimated baseline muscle weakness. Main Outcome Measurements: Knee extensor and flexor and ankle dorsiflexor muscle strength were measured annually with a Biodex dynamometer. Results: The men (n = 28) had significant linear change over time for all knee muscle strength measurements, from −1.4% ( P < .05) per year for isokinetic knee flexion in the less‐affected lower limb to −4.2% ( P < .001) for isokinetic knee extension in the more‐affected lower limb, and for 2 ankle dorsiflexor muscle strength measurements (−3.3%‐1.4% per year [ P < .05]). The women (n = 24) had a significant linear change over time only for ankle dorsiflexor measurements (4.0%‐5.5% per year [ P < .01]). Gender was the strongest factor that predicted a change in muscle strength over time. Conclusions: Over 4 years, men had a greater decline in muscle strength than did women, but the rate of decline did not accelerate. This finding indicates that gender could be a contributing factor to the progressive decline in muscle strength in persons with late effects of polio.